Review of Instructional Digital Media to Path Teachers’ Digital Competence on Philosophical Perspective: Distraction or Diversion - Ismail, Syofianis; Ling, Zhang; Nawir, Erna; Alber, Alber; Fauziah, Desna (International Journal of Education and Digital Learning (IJEDL), 2023)
In spite of its emergence in 1980s, digital media has been well known to this day, yet it is still questioned whether its presence is merely a "disturbance" or a "diversion" after contradictory impacts of digital media usage have been found based on several conducted studies. Answering the question, library research was carried out by using some sources and references in getting and analyzing the data. Then, the writers integrated their ideas by synthesizing in drawing conclusion. Delving into the essence of four learning theories (behaviorism, cognitivism, constructivism, and connectivism) and their integration with technology, particular media use and their functions are recognized through a systematic procedure in certain digital learning approach as one alternative for teachers in selecting and utilizing digital media in learning process. It was found that, firstly, the comprehension basic learning philosophy serves as fundamental reasons for teachers in utilizing technology. Secondly, the learning theories play as the base for teachers to develop their teaching approaches by maximizing their digital competence through digital technology use for improving their digital literacy. Lastly, the ownership of knowledge and skill for instructional digital media use develops teachers’ digital competence by recognizing students’ need in learning. In a nutshell, the choice for digital media utilization has to be supported by understanding the intensive relation between teachers and their learners’ roles and the instructional strategies in integrating media and technology used which will awaken not only teachers’ digital literacy, but especially their digital competence as well, as displayed through their ability to be intricately connected to digital media use. Therefore, the comprehensive understanding of learning theories approach of teachers and their ways in utilizing media-based technology determines the function of the media itself whether it is distraction or diversion during teaching and learning process.